2015
DOI: 10.1089/pho.2014.3824
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of 940 nm Laser on Gamma-Irradiated Mice

Abstract: Objective: The purpose of this study was to investigate the radioprotective features of 940 nm laser on the life span of mice, and absolute counts of blood cells and their proportions in gamma-irradiated mice. Background data: An important feature of laser light is activation of mitotic division and differentiation of cells, which may be useful in activation of hematopoiesis in gamma-irradiated organisms. Materials and methods: Mice were randomly assigned to 11 groups according to the type(s) of influence. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…As a result of this impact, the mice in group C had a greater number of WBCs than the mice in group B. This effect of laser therapy corresponded with results from our previous experiment [20] and may have led to the more effective regeneration of hematopoiesis and the prolonged lifespan of mice even after irradiation with a lethal dose of gamma radiation.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As a result of this impact, the mice in group C had a greater number of WBCs than the mice in group B. This effect of laser therapy corresponded with results from our previous experiment [20] and may have led to the more effective regeneration of hematopoiesis and the prolonged lifespan of mice even after irradiation with a lethal dose of gamma radiation.…”
Section: Discussionsupporting
confidence: 85%
“…We did not organize a group of healthy mice irradiated with laser radiation only, because the primary aim of our study was to explore the effectiveness of laser treatment in the recovery of leukopoiesis post-irradiation and proposed that such a group would not provide direct information relevant to this specific research question. In our prior research we had already demonstrated that high-power laser treatment can reduce the counts of certain peripheral blood cells (absolute counts of white blood cells, lymphocytes, neutrophils, and monocytes) in a dose-dependent manner [20]. These fallouts helped us to explain the results in the group irradiated by gamma radiation 24 h after laser therapy [20].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations